2018
DOI: 10.1162/jocn_a_01189
|View full text |Cite
|
Sign up to set email alerts
|

Got Rhythm? Better Inhibitory Control Is Linked with More Consistent Drumming and Enhanced Neural Tracking of the Musical Beat in Adult Percussionists and Nonpercussionists

Abstract: Abstract■ Musical rhythm engages motor and reward circuitry that is important for cognitive control, and there is evidence for enhanced inhibitory control in musicians. We recently revealed an inhibitory control advantage in percussionists compared with vocalists, highlighting the potential importance of rhythmic expertise in mediating this advantage. Previous research has shown that better inhibitory control is associated with less variable performance in simple sensorimotor synchronization tasks; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 66 publications
3
25
0
1
Order By: Relevance
“…Rhythm is an important component of music that has been used in MT interventions to address a range of needs associated with various disorders (Aldridge, 1996;Berger, 2012;Faulkner, 2017;Hanser, 2016;Thaut et al, 2014;Tierney & Kraus, 2014). Rhythm-based MT interventions are hypothesized to utilize the process of entrainment-the coordination of the internally generated rhythm of an individual with an external rhythm-to organize motor and neural activity through patient interaction with a structured musical pulse (Berger, 2016;Slater, Ashley, Tierney, & Kraus, 2018;Thaut et al, 2014;Thut, Schyns, & Gross, 2011;Tierney, White-Schwoch, MacLean, & Kraus, 2017). Motor entrainment is potentially explicitly driven in active but not passive MT interventions, which instead emphasize passive listening without motor coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Rhythm is an important component of music that has been used in MT interventions to address a range of needs associated with various disorders (Aldridge, 1996;Berger, 2012;Faulkner, 2017;Hanser, 2016;Thaut et al, 2014;Tierney & Kraus, 2014). Rhythm-based MT interventions are hypothesized to utilize the process of entrainment-the coordination of the internally generated rhythm of an individual with an external rhythm-to organize motor and neural activity through patient interaction with a structured musical pulse (Berger, 2016;Slater, Ashley, Tierney, & Kraus, 2018;Thaut et al, 2014;Thut, Schyns, & Gross, 2011;Tierney, White-Schwoch, MacLean, & Kraus, 2017). Motor entrainment is potentially explicitly driven in active but not passive MT interventions, which instead emphasize passive listening without motor coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviorally, musicians are better than controls at rhythm perception and temporal discrimination tasks (Rammsayer and Altenmüller, 2006 ; Wallentin et al, 2010 ) and have more consistent sensorimotor timing (Repp and Su, 2013 ). They also demonstrate enhanced cognitive function, including attention, inhibitory control and working memory (see Benz et al, 2015 , for recent review), with enhanced inhibitory control linked to more consistent sensorimotor timing (Slater et al, 2017 , 2018 ). Researchers found that musicians had larger volumes in motor areas including the cerebellum and basal ganglia, as well as frontal and parietal regions associated with cognitive control (see Schlaug, 2015 , for review), and music training has been associated with functional changes to oscillatory dynamics (Bhattacharya and Petsche, 2005 ; Trainor et al, 2009 ).…”
Section: Effects Of Expertisementioning
confidence: 99%
“…It is possible that group comparisons reflect innate differences in those drawn to pursue music rather than causal effects of training, in fact there is some preliminary evidence showing increased expression of dopamine receptors in musicians compared with controls, suggesting a potential genetic tendency toward musicianship (Emanuele et al, 2010 ). However, evidence from longitudinal studies (Moreno et al, 2011 ; Roden et al, 2014 ) as well as links between behavioral enhancements, extent of expertise (Slater et al, 2018 ) and specific instrument played (Krause et al, 2010 ) suggest that experience plays at least some role in observed differences. Further, therapies focusing on motor timing or rhythm have shown some success in ameliorating the broader symptoms of ADHD (Shaffer et al, 2001 ; Leisman and Melillo, 2010 ; Dahan et al, 2016 ), although more intervention studies are needed.…”
Section: Effects Of Expertisementioning
confidence: 99%
“…Indeed, some researchers have suggested that it is specifically the sensorimotor aspects of musical training that could strengthen overlapping neural networks for attention and cognition. For instance, a recent study suggested that rhythmic expertise, built via long-term percussion training, shaped attentional and inhibitory control ( Slater et al 2018 ). Others have suggested that long-term instrument training could lead to an automation of task-specific cognitive processes, for instance, those involved in creating new musical sequences and combinations ( Pinho et al 2014 ).…”
mentioning
confidence: 99%